The specifics of the art autobiography genre - Ibrayeva, Danara; Salkhanova, Zhanat; Joldasbekova, Bayan; Bayanbayeva, Zhadyra (Opción, 2018)
The prominent feature of the writings of prose in recent decades in Kazakh is the role of the writer's personal life in the formation of literary works, so that the literature of this period can be called the "autobiography". In the article the conclusion that the art autobiography represents a special genre in literature is formulated. The authors of the article consider that the work based on the documentary facts from the writer's life which turn into artistic characters and become not only the subject, but also the object of the character should be referred to such a genre.